FASHION PRODUCT IS HUMAN: Structural Metaphor as a Linguistic Strategy for Second Hand Fashion Products on Live Commerce in Indonesia - Yoga Yolanda; Budi Setyono (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study aims to describe the structural metaphors employed by second-hand fashion product shop hosts on live commerce. The qualitative research was carried out by collecting data through the free-participation listening technique on live commerce activities, then continuing with semi-structured interviews with live commerce shop hosts. Live commerce used as a place to collect data was Shopee Live. The collected data was checked for data validity through language expert validation. The present study employed data analysis techniques from the cognitive semantics perspective. The findings indicated that cross-medium communication during the procurement and disposition of secondhand fashion products in live commerce fosters a distinct personification tendency in the conceptualization of